In silico mining for alkaline enzymes from metagenomic dna data of gut microbes of the lower termite Coptotermes gestroi in Vietnam - Giang, Nguyen Minh; Huyen, Do Thi; Hai, Truong Nam (Academia Journal of Biology, 2016)
The high alkaline proteases, lipases, cellulases and hemicellulases are important enzymes in research and industries. In this study, using the Alcapred software, the metagenomic DNA sequences of  the gut flora of Coptotermes gestroi were analyzed to identify the enzymes that were specifically adapted to alkaline condition. The results show that 737 of 943 ORFs (accounting for 72%) encoded proteases, 154 of 214 ORFs (holding 78%) encoded lipases and 338 of 575 ORFs (accounting for 59%) encoded cellulase and hemicelluase. All those enzymes were predicted to be alkaline enzymes. This study provide an overview picture of the alkaline enzyme groups of the gut flora of C. gestroi, and provide a good database for mining, isolation of the genes to produce recombinant enzymes.